THE INFLUENCE OF SERVICE QUALITY, INNOVATION, CORPORATE IMAGE, AND CUSTOMER SATISFACTION ON REPURCHASE INTENTION THROUGH LOYALTY-BASED SUSTAINABLE COMPETITIVE ADVANTAGE OF BRIGUNA CREDIT CUSTOMERS AT BANK BRI IN THE TAPAL KUDA REGION, EAST JAVA - Setiyo Adi (PT. Jurnal Center Indonesia Publisher, 2026)
The existence of banking institutions has an important role in the country's economy. Banking institutions have three main functions, namely financial intermediary, agent of development and agent of trust. The existence and sustainability of banking institutions must be pursued as much as possible by bank managers, because their existence can improve the economy. One of the efforts made by banking institutions is to channel credit to parties in need to meet customer needs and obtain benefits for banking institutions. The research method includes explanatory-descriptive-quantitative research. The population is 24,675 consumer credit customers of BRIGuna Bank BRI in the horseshoe area, East Java. The sample is 250 customers who have received BRIGuna consumptive credit at least twice in a row, using non-probability sampling-purposive sampling on a quota basis. Analysis tools and techniques using SPSS, SEM, and AMOS version 24. Data collection techniques using a questionnaire / google form and interviews. Service quality and innovation of a bank will improve the company's image, sustainable competitive advantage based on loyalty and the intention to re-elect in one bank. Innovation also affects customer satisfaction, while loyalty-based sustainable competitive advantage is also influenced by the image of banking companies. Loyalty-based sustainable competitive advantage affects the intention to re-elect in a bank. Further research to be more specific on the quality of consumer credit services, requires a collaborative approach to customers which is social capital and focuses on innovation that provides convenience for customers while maintaining the company's image in the eyes of customers because this is the key to a loyalty-based sustainable competitive advantage.